Testing Travel Intention Model: An Empirical Study of Borobudur Temple - Sabrina O. Sihombing, Elvin Alvandi, Dellazenda, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This research aims to test the travel intention model that includes several main variables in predicting travel intention. Specifically, Borobudur temple was used to test the model because the temple was one of world heritage. Respondents were chosen by judgemental sampling and the sample size was 240. This research applied structural equation modelling to test research hypotheses. All research hypotheses were supported by data. This manuscript provide the literature review along with the development of hypotheses, research method, results and discussion, and research limitations and conclusion.